(I)legitimidade do direito de ingerência: uma análise a partir da Teoria Crítica dos Direitos Humanos - Cogo, Rodrigo (2011)
The present dissertation investigates the legitimacy of invocation of an alleged Right to Interference with the use of military force for the protection of human rights. The work performs a conceptual analysis of the institution of humanitarian intervention clearing their historical and doctrinal origins, as well as the moral foundation of today\'s practice of interventions carried out by States, individually or in alliance with their peers within other sovereign states. It argues that under the auspices of the tragic results of the Second World War, with the emergence of the United Nations and, with the vast legal production produced during the twentieth century, there was an unprecedented process of internationalization of the recognition, protection and promotion human rights beyond the territorial boundaries of states, however, the current situation is of some complexity to create a dilemma involving on the one hand, the regime of international protection of human rights, settled by the preamble of the UN Charter, and on the other dogmas of State sovereignty and non intervention in its domestic jurisdiction, also established by the UN document. The study also offers a special focus on the important role played by the Security Council of the United Nations in interventions, since it is endorsed by the actions that occur with the use of force. In order to expose the apparent incompleteness of the issue involving the interference on behalf of human rights, the proposal is also a critical examination of both the content of universalizing of human rights, and the amazing symbolism that can take a humanitarian. Nonetheless, it is argued that if different actions are implemented in the scenario of law and international relations, will be able to talk about legitimacy is not only a right but rather a duty to intervene. In this context, using the deductive method, this documentary and bibliographical research has the power to examine the legitimacy or otherwise of the institute the right of interference as it has been invoked in the contemporary legal landscape, based on a critical human rights. It is hoped with this study, contribute to the debate about the legitimacy or otherwise of humanitarian interventions, attracting attention to the unique need for dialogue between different cultures in dealing with issues involving human dignity.